Surviving in the Workplace: Conditions in Centres for the Prevention and Treatment of Drug Addiction - Liljana Ignjatova (AU-CNS, 2019)
Background. The European Commission has adopted a new Strategic Framework on Health and Safety at Work, 2014- 2020 and the prevention of physical accidents has recently been expanded to include the prevention of mental accidents. Aim of this study is to show the workplace situation in centres for the prevention and treatment of drug addiction (CPTDAs). Methods. The survey was conducted in 2014/2015 in 12 CPTDAs in the Republic of Macedonia. The unstandardised, work-related questionnaires were prepared by staff at the CPTDAs, in each case with a related workshop, where 31 participants were asked to analyse data through group work. Results. The number of patients participating in the study was 1,314, their average methadone dose varied from 53 to 99 mg, with 0%-60% injecting drugs in the last 30 days; 0%- 26% were employed and 0%-70% needed social help from the various centres involved. The staff complained that there were: aggressive patients, threats, offensive remarks, attempts by patients to blackmail staff members and their family, thefts carried out by patients, obstruction of the professional work being done by staff, incomplete teams, too few psychiatrists and doctors, an insufficient availability of medications for the treatment of comorbidity, an insufficient supply of buprenorphine, difficulties in referring patients to psychiatric and other hospitals, poor quality of security staff, large numbers of patients, poor quality of packaging bottles for take-home therapy, too few screening tests, inflexible working hours, organisational problems, having to face a strong social stigma, insufficient support, work to be done over the weekend for prison staff only and insufficient rest. Conclusions. Adequate care of staff is needed if our aim is to adequately cure patients.
Keywords: safe and health workplace; surviving in the workplace; AOT programmes